An evaluation of the SACLA Rehabilitation Worker project in Cape Town, South Africa, 1992-1993 - Loveday, Marian Patricia (Department of Paediatrics and Child Health, 2018)
This dissertation reports on an evaluation of the home visiting programme of the SACLA Rehabilitation Worker project against the background of the socio-economic context of the community and the history of the project. The evaluation had two aims. Firstly, it aimed to highlight the programme's strengths and weaknesses so that the work could become both more efficient and more effective. Secondly, it aimed to establish whether the SACLA rehabilitation project is an effective model of a community based rehabilitation project on which other local projects could be based. Quantitative data was collected by interviewing the caregivers of disabled children who were involved in the project. In-depth interviews with the rehabilitation workers provided qualitative data which was used to confirm the validity of some of the quantitative data. The foremost findings were that the mothers were very positive about the support received from the RWs. The majority of the caregivers remembered the activities that they had been taught by the RWs and performed them well. Poor communication with the caregivers and a lack of skills on the part of the RWs gave rise to a number of problems. A number of changes highlighted by the evaluation were suggested. In conclusion, the project was found to be an effective model of local community based rehabilitation on which other projects could be based.